Land Use Suitability for Spatial Planning in Salatiga City - Delia Puspita; Nugroho Adi Kurniawan; Imam Bagus Mulyanto (Jurnal Planologi, 2026)
Land use changes in urban areas are a consequence of the increasing population, economic dynamics, and the need for built-up space. Salatiga City is strategically located in the Semarang-Solo-Yogyakarta corridor, which is experiencing rapid regional development, thus driving spatial transformation in various sectors. Population growth and demand for housing development have led to the conversion of agricultural land into residential areas, while increased industrial activity has also increased the need for non-agricultural land. Land use changes have been quite significant in the last decade, with an increase in residential areas from 1,744.85 hectares in 2014 to 1,949.92 hectares in 2024. On the other hand, there has been a decrease in agricultural land area, both wet and dry land, along with the increasing need for built-up space. This study aims to analyze the suitability of land use to the spatial planning of Salatiga City. The research method uses a quantitative descriptive approach through overlay analysis between the 2024 land use map and the Geographic Information System (GIS)-based spatial pattern plan and the in-table building exchange (ITBX) matrix. The analysis results show that the most dominant non-conformities are in the Local Protection zone (39.52 ha) and the Food Crop zone (2.77 ha) which have been converted into residential and commercial areas. This study provides spatial integration with the ITBX matrix that allows for flexible suitability assessments and these findings confirm that spatial non-conformities are the result of the interaction between development pressures, accessibility and governance limitations. Broader implications show the importance of strengthening spatial data-based spatial planning control and increasing institutional capacity in dealing with urbanization pressures in developing cities. Keywords: Land Use, Spatial Planning Suitability, Salatiga City  Perubahan penggunaan lahan di wilayah perkotaan merupakan konsekuensi dari meningkatnya jumlah penduduk, dinamika ekonomi, serta kebutuhan terhadap ruang terbangun. Kota Salatiga menjadi posisi strategis pada koridor Semarang-Solo-Yogyakarta yang mengalami perkembangan wilayah yang cukup pesat sehingga mendorong transformasi ruang pada berbagai sektor. Pertumbuhan penduduk dan permintaan pembangunan perumahan menyebabkan konversi lahan pertanian menjadi kawasan permukiman, sementara peningkatan aktivitas industri turut memperbesar kebutuhan terhadap lahan non-pertanian. Perubahan penggunaan lahan yang cukup signifikan dalam satu dekade terakhir, peningkatan kawasan permukiman dari 1.744,85 hektare pada tahun 2014 menjadi 1.949,92 hektare pada tahun 2024. Di sisi lain, terjadi penurunan luas lahan pertanian, baik tanah basah maupun tanah kering seiring meningkatnya kebutuhan ruang terbangun. Penelitian ini bertujuan untuk menganalisis kesesuaian penggunaan lahan terhadap penataan ruang Kota Salatiga. Metode penelitian menggunakan pendekatan deskriptif kuantitatif melalui analisis overlay antara peta penggunaan lahan tahun 2024 terhadap rencana pola ruang berbasis Sistem Informasi Geografis (SIG) serta matriks in table building exchange (ITBX). Hasil analisis menunjukkan ketidaksesuaian paling dominan terdapat pada zona Perlindungan Setempat (39,52 ha) dan zona Tanaman Pangan (2,77 ha) yang telah beralih menjadi kawasan permukiman maupun perdagangan. Penelitian ini memberikan integrasi spasial dengan matriks ITBX yang memungkinkan penilaian kesesuaian secara fleksibel serta temuan ini menegaskan bahwa ketidaksesuaian tata ruang merupakan hasil interaksi antara tekanan pembangunan, aksesbilitas dan keterbatasan tata kelola. Implikasi yang lebih luas menunjukkan pentingnya penguatan pengendalian tata riang berbasis data spasial dan peningkatan kapasitas kelembagaan dalam menghadapi tekanan urbanisasi di kota-kota berkembang.Kata Kunci: Penggunaan Lahan, Kesesuaian Tata Ruang, Kota Salatiga